REFORMING THE UNITED NATIONS: REALITIES, EXPECTATIONS, AND THE WAY FORWARD - Joy Henri Mangapul (International Law Department, Faculty of Law Universitas Padjadjaran, 2019)
AbstractThe United Nations was born as an end-result of the Second World War. Its stated purpose was obvious as enshrined in the Charter of the United Nations (“the Charter”) – to maintain international peace and security. The United Nations, however, both in terms of practicality and the will to do such, had been burdened by several problems surrounding them; the ineffectiveness of several bodies such as the Trusteeship Council, the Economic and Social Council (“ECOSOC”), etc.; the overwhelming power of the veto rights vested towards the five permanent members of the United Nations Security Council (